A holistic approach for performance assessment of personal rapid transit. (March 2016) - Mascia, M.; Hu, S.; Han, K.; Sun, A.; North, R.; Lees-Miller, J.D.
Abstract: Personal Rapid Transit (PRT) has received increased attention in recent years due to technological innovation and the need for safer, more efficient, and more sustainable transport systems in dense urban areas. PRT service is on demand, and provides a good level of service due to short waiting time with no intermediate stops. The cost to run the system is lower compared to traditional transport systems due to utilizing autonomous pods. While a number of studies have focused on specific aspects of the performance of PRT, there is still a lack of comprehensive assessment of PRT's performance from the perspectives of both operators and users. This paper addresses this gap by proposing a set of PRT-specific Key Performance Indicators (KPI) relevant to its operational characteristics (e.g. pod utilization, total distance travelled) and user experience (e.g. average waiting time, delay). The proposed KPIs are demonstrated through a simulation study. The findings made in this paper constitute the first step towards comprehensive benchmarking for PRT systems, and facilitate comparative analyses of different PRT systems to help operators identify and implement best practise.